The role of carbon tax in the integration of environmental economy and green economy in Indonesia - Resty Abdillah Paryanda; M. Agus Alfiyan Nur Ahmada; Cindy Wakhidatul Maqfiroh (Privietlab, 2026)
Indonesia's rapid economic growth over the past two decades has had a significant impact on the increase of greenhouse gas (GHG) emissions, creating an urgency to integrate environmental dimensions into national economic policies. This study aims to analyze the role of carbon taxes as an instrument connecting environmental economics and the green economy framework in Indonesia. The method used is descriptive quantitative combined with policy analysis, allowing for the mapping of carbon emission conditions, energy structure, and the evaluation of carbon tax implementation in the context of sustainable development. Secondary data were obtained from BPS, KLHK, the Ministry of Energy and Mineral Resources, as well as official policy documents related to carbon taxes and green fiscal measures. Research results show that the energy sector remains the main contributor to GHG emissions, with a high dependence on coal, resulting in relatively high carbon intensity. The initial imposition of a carbon tax rate of IDR 30,000 per ton of CO₂e provides only a limited price signal in driving changes in industrial behavior. Integrative analysis confirms that carbon taxes have strategic potential to promote green investment, energy efficiency, and structural transformation towards a low-carbon economy. However, their effectiveness depends on progressive policy design, institutional readiness, and fair revenue allocation. Compared to the current situation, the implementation of a carbon tax still faces socio economic and technical challenges, including a limited MRV system and the potential regressive impact on low income households.